Investigation of Electrochemical Behaviour of Aminophenol Diazonium Salt Covalently Grafted onto the Glassy Carbon Electrode Surface - Ender Mulazimoglu, Ibrahim (Asian Journal of Chemistry, 2011)
In this paper, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) have been used to investigate of the electrochemical behaviour of aminophenol diazonium salt on the modified glassy carbon (GC) electrode. The modification of aminophenol diazonium salt covalently grafted onto the glassy carbon electrode surface was performed between +0.1 and -0.9 V potential ranges for cathodic scan, 0.0 and +1.7 V potential ranges for anodic scan of 0.1 V s-1 and 10 cycles.